8051 microcontrollers an applications-based introduction - Calcutt, D. M., 1935-
In this book the authors introduce the fundamentals and capabilities of the 8051, then put them to use through practical exercises and project work. The result is a highly practical learning experience that will help a wide range of engineers and students to get through the steepest part of the learning curve and become proficient and productive designing with the 8051. The text is also supported by practical examples, summaries and knowledge-check questions. The latest developments in the 8051 family are also covered in this book, with chapters covering flash memory devices and 16-bit microcontrollers.